Medical adherence in patients with systemic lupus erythematosus in Germany: predictors and reasons for non-adherence – a cross-sectional analysis of the LuLa-cohort. (September 2018) - Chehab, G; Sauer, G M; Richter, J G; Brinks, R; Willers, R; Fischer-Betz, R; Winkler-Rohlfing, B; Schneider, M
Objective: Adherence to medication has a major impact on treatment control and success especially in chronic diseases but often remains unrecognized. Besides clinical, socioeconomic, disease-related and treatment-related parameters, general and personal health beliefs, as well as perception of health, can affect adherence. Our aim was to investigate the adherence to lupus-specific medications in German lupus patients and to assess influencing factors including detrimental or beneficial effects of health perceptions and beliefs. Methods: The Lupus Erythematosus (LE) Long-Term Study (LuLa-study) is a nationwide longitudinal study among German Caucasian patients with systemic lupus erythematosus who have been assessed annually using a self-reported questionnaire since 2001. In 2013, we included questions concerning medical adherence (Morisky Medication Adherence Scale; MMAS-4), beliefs about medication prescribed (BMQ), illness perception and about the patients' health locus of control (HLC). We present a cross-sectional analysis to assess predictors of adherence using a multivariable stepwise logistic regression. Results: Five hundred and seventy-nine patients participated, 81 of whom did not take any lupus-specific medication and 40 of whom did not complete the MMAS-4 and were therefore omitted. Only 62.7% reported high adherence. Unintentional behaviour for low medical adherence exceeded the intentional behaviour by far. The use of azathioprine (OR: 1.85; 95% CI: 1.02–3.34), prednisone <7.5 mg (OR: 1.56; 95% CI: 0.97–2.49), a higher age (OR: 1.06; 95% CI: 1.03–1.08) and higher external HLC (OR: 1.15; 95% CI: 1.01–1.30) proved conducive for high adherence in our multivariable model. On the contrary, the general perception of medication being harmful or addictive (OR: 0.89; 95% CI: 0.82–0.97) was detrimental. Conclusion: A low belief that one's own health is determined by healthcare providers (external HLC) and the belief of the harmfulness of medication were independent predictors of low adherence besides age and the choice of the medical agent. The recognition of these potential obstacles in physician–patient relationships is essential to ameliorate adherence. Provision of sufficient information and education might help to reach the best possible outcome.